A magnetic nanofiber-based zwitterionic hydrophilic material for the selective capture and identification of glycopeptides. Issue 22 (29th May 2019) - Huan, Weiwei; Zhang, Jingshu; Qin, Heng; Huan, Fei; Wang, Buchuan; Wu, Minjie; Li, Jie
Abstract : A magnetic nanofiber-based zwitterionic hydrophilic material with excellent performance and practical potential for capturing and identifying glycopeptides has been developed. Abstract : High-performance affinity materials are highly required in the sample preparation process in mass spectrometry-based glycoproteomics studies. In this research, a novel magnetic nanofiber-based zwitterionic hydrophilic material is prepared for glycopeptide enrichment and identification. The one-dimensional hydroxyapatite nanofiber (HN) acted as the supporting substance for immobilizing both Fe3 O4 nanoparticles and Au nanoparticles, following the surface modification with a zwitterionic tripeptidel -glutathione (GSH) via the affinity interactions between the thiol group in GSH and both Au and Fe3 O4 to form the magHN/Au-GSH nanofiber. Owing to the unique structural features, excellent hydrophilicity, abundant zwitterionic molecules, and strong magnetic responsiveness, the as-prepared magHN/Au-GSH nanofiber possesses satisfactory specificity for glycopeptide enrichment. As a result, the magHN/Au-GSH nanofiber demonstrated great detection sensitivity (2 fmol), satisfying enrichment recovery (89.65%), large binding capacity (100 mg g −1 ), and high enrichment selectivity (1 : 100) toward glycopeptides. Furthermore, 246 N -glycosylated peptides corresponding to 104 N -glycosylated proteins were identified from only 1 μL human serum, revealing the great potential of this affinity nanofiber for glycopeptide enrichment and glycoproteomics research.